2015
DOI: 10.4049/jimmunol.1500638
|View full text |Cite
|
Sign up to set email alerts
|

Chicken STING Mediates Activation of the IFN Gene Independently of the RIG-I Gene

Abstract: Stimulator of IFN genes (STING) is an adaptor that functions downstream of retinoic acid–inducible gene I (RIG-I) in mammalian cells; however, RIG-I is absent in chickens. We identified chicken STING (chSTING) as a critical mediator of virus-triggered type I IFN signaling in RIG-I–null chicken cells. Overexpression of chSTING in DF-1 cells inhibited Newcastle disease virus and avian influenza virus (AIV) viral replication and activated IRF-7 and NF-κB to induce expression of type I IFNs. Knockdown of endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 44 publications
6
87
0
Order By: Relevance
“…However, in some RIG-I-null species, such as chicken and Chinese tree shrew, MITA can interact with MDA5 to mediate the corresponding signaling. Knockdown of MITA inhibits MDA5-mediated IFN-β activation (9, 19). Therefore, experimental evidence needs to be proposed to identify whether MITA is essential for MDA5 signaling pathway in RIG-I-existed species and compare the difference between RIG-I- and MDA5-mediated MITA downstream signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some RIG-I-null species, such as chicken and Chinese tree shrew, MITA can interact with MDA5 to mediate the corresponding signaling. Knockdown of MITA inhibits MDA5-mediated IFN-β activation (9, 19). Therefore, experimental evidence needs to be proposed to identify whether MITA is essential for MDA5 signaling pathway in RIG-I-existed species and compare the difference between RIG-I- and MDA5-mediated MITA downstream signals.…”
Section: Discussionmentioning
confidence: 99%
“…Both RIG-I and MDA5 can sense a wide variety of RNA or DNA viruses (1, 7). Upon viral recognition, RIG-I and MDA5 activate nuclear factor κB (NF-κB) and interferon regulatory factor 3 (IRF3) through the adaptor proteins IFN-β promoter stimulator 1 [(IPS-1), also known as MAVS, VISA, or Cardif] and mediator of IRF3 activation [MITA, also named as STING] (8, 9). IPS-1 is a CARD domain-containing protein that drives the expression of type I interferons (IFN-Is) and inflammatory cytokines (1).…”
Section: Introductionmentioning
confidence: 99%
“…Chickens lack the RIG-I gene ddx58 (41), and IFN induction is mediated by the related RNA helicase and PRR, MDA5 (36). In contrast to mammalian STING, chicken STING forms a complex with MDA5 (and the MAVS adaptor) to induce IFN at later stages of FLUAV infection (42). Moreover, chicken MDA5 was recently identified to sense short dsRNAs, just like mammalian RIG-I (but unlike mammalian MDA5) does (43).…”
Section: Rig-i-independent Cytoplasmic Responses and Fluav Countermeamentioning
confidence: 99%
“…Previous studies suggested that TRAF6 is a crucial cytoplasmic adaptor molecule responsible for the pathogen-recognition receptors (PRR)-mediated innate immune response (Bradley and Pober, 2001). The tissue distribution of TRAF6 is an important determinant of its function, and can influence the capacity of cells to detect different microorganisms during different periods in different tissues (Cheng et al, 2015). The tissue distribution of TRAF6 has been previously examined in humans (Starczynowski et al, 2011), mice (Mason et al, 2004), and ducks (Zhai et al, 2015).…”
Section: Discussionmentioning
confidence: 99%